A Case of Abruptio Placentae due to the Torsion of Gravid Uterus. (4th December 2014) - Zullino, S.; Faiola, S.; Paganelli, A. M.; Ferrazzi, E.
Abstract : Torsion of a gravid uterus is a rare obstetric emergency potentially lethal for the fetus and the mother. Some of the cases described in literature are associated with preexisting gynecologic conditions related to pelvic and uterine anatomy, even if most of cases remain unexplained. We report a case of acute 180-degree torsion of uterus at 33 weeks of gestation associated with abruptio placentae in a young Asian woman without apparent risk factors.